Occlusal features of 5-year-old Greek children: a cross-sectional national study - Sotiria Davidopoulou; Konstantinos Arapostathis; Elias D. Berdouses; Katerina Kavvadia; Constantine Oulis (BMC, 2022)
Abstract Background Occlusal characteristics of the primary dentition are crucial in predicting and determining permanent tooth alignment and occlusion. The aim of our study was to determine the occlusal characteristics of the primary dentition of 5-year-old children in Greece through a national pathfinder survey. Methods A stratified cluster sample of 1222 5-year-old children was selected according to the WHO guidelines for national pathfinder surveys. Five occlusal traits were registered clinically in centric occlusion, separately for the left and right sides: sagittal relationships of the second primary molars and primary canines, overjet, overbite, crossbite, and maxillary and mandibular spacing. Results Most children showed a flush terminal plane of primary second molars (44.8%), a class I primary canine relationship (52.2%) and normal overjet (46.4%), but a high prevalence of Class II canine relationship (25.6%) and overjet (37.8%) were also observed. A normal overbite was found in 40% of the children and 40% had a deep overbite. Spacing was apparent in both maxilla (71.1% of children) and mandible (56.4%). The prevalence of open bite and distal step molar relationship significantly rose in children with non-nutritive sucking habits. Conclusions Νon-nutritive habits were associated to altered occlusal features. No sex significant differences were found in either the sagittal relationships of second primary molars and primary canines, or overjet, overbite, crossbite and spacing.